http://www.odermatol.com/issue-in-html/2017-3-2-pattern - Abdulghani Mohamed Alsamarai; Shler Ali Khorshed; Hajer Ali (Our Dermatology Online, 2017)
Background: Urinary tract infection is the most common community and hospital bacterial infection and characterized by high rate of treatment failure and recurrences. Aim: to determine the association between risk factors and bacterial type. Materials and Methods: A prospective cross-sectional study conducted during the period from 1st of June 2015 to the end of January 2016. The population included in the study are 563 women, of them 425 (75.5%) were outpatients, and 138 (24.5%) were inpatients. Their age range between 18 and 80 years, with a mean age of 33.59±15.29 years. Urine samples were immediately cultured on blood agar and MacConkey's agar by spread plate technique. Bacterial colonies with different morphology were selected, purified and identified according to their biochemical characteristics using conventional standard methods. Results: Mean age was significantly (F=5.14, P=0.002) different in relation to bacterial type. Women infected with E. coli were with higher mean age (37.84 year), followed by those infected with Staphylococcus aureus (31.97 year), then Klebsiella pneumonia (28.76 year) and Proteus mirabilis (28.50 year). BMI mean value was significantly (F=6.33, P=0.000) different in women infected with different bacteria and higher value was in those infected with E. coli (26.15), while it was about the same in those infected with Staphylococcus aureus (24.6), then Klebsiella pneumonia (24.9 year) and Proteus mirabilis (24.1). Pus cell scale mean value was significantly (F=6.67, p=0.000) higher in cases infected with E. coli (2.04), while 1.77 in Staphylococcus aureus, infected cases, 1.15 in women infected with Klebsiella pneumonia and 1.33 in those infected with Proteus mirabilis. Conclusion: Age, BMI, pus cells scale, and education levels were significantly associated with bacterial type.